PENERAPAN GUIDED DISCOVERY LEARNING MODE DARING UNTUK MENGEMBANGKAN PRESTASI BELAJAR SISWA PADA MATERI MATRIKS DI KELAS XI SMA NURUL JADID - Siti Anisah (JUSEDA, 2020)
Anisah, Siti. 2020. The applying of Guided Discovery Learning Daring Mode to develope the students’ achievement learning on matrix in the senior high school of NURUL JADID. Article, Teacher Profesional Education Department, Faculty of Mathematic and Science, Muhammadiyah University of Gresik. Advisors: Dr.Irwani Zawawi, M.Kes. This study describes the design and implementation of mathematics learning using Guided Discovery Learning to see the learning achievement of class XI students in the senior high school of NURUL JADID on the matrix material. The results of this classroom action research indicate that the percentage of the number of students who completed learning in cycle 1 was 30.8% while the percentage of the number of students who completed learning in cycle 2 was 57.7% and the percentage of the number of students who completed learning in cycle 3 was 84.6 %. According to the completeness of learning determined by SMA NURUL JADID, the implementation of learning is said to be supportive or successful if at least 80% of students get a minimum score of 75 so that in this case it can be concluded that learning with Guided Discovery Learning in this study is successful. This can be strengthened by the results of observations of student activities that fall into the "Very Good" category in cycle 1, cycle 2 and cycle 3.